Genetic basis of melanoma: own investigations and literature review - Lamperska, Katarzyna; Przybyła, Anna; Kaczmarek, Aldona; Leporowska, Ewa; Mackiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2006)
Melanoma like other cancers is a genetic disease including involvement of environmental factors and genetic predisposition. The genetic base of melanoma is the subject of intensive investigations carried out by different scientific centers during the past few years. Till now some genes have been recognized belonging to suppressor genes pathway of p16(CDKN2a)- - CDK4-Rb and ARF-HDM-p53 and pathway of signal transduction connecting with activated mutations in RAS and BRAF genes. Described in literature mutations determine only % of all melanomas and are not regarded as the general model of carcinogenesis. For a few years, new genes have been introduced to melanoma diagnostics. Here we report current knowledge about melanoma genetics based on our own experience and literature.